Recovery of acetic acid from aqueous solutions using salting effect - Aidaoui, Ahleme; Hasseine, Abdelmalek (Journal of Applied Engineering Science & Technology; Vol 4 No 1 (2018), 2018)
The application of salting effect to isolate an organic acid, particularly Acetic acid, from aqueous solution is reported. In fact the presence of a salt can influence the solubility of a compound by either increasing it or decreasing it, leading to Salting-in and Salting-out, respectively. The addition of a salt in an aqueous solution introduces ionic forces which affect liquid-liquid equilibrium and which influence directly the distribution coefficient of the solute. The effect of NaCl and Na 2 SO 4 on the liquid-liquid equilibrium data of the ternary system (Water+ Acetic Acid+ Dichloromethane) at a temperature of 293.15 K and an atmospheric pressure is studied experimentally in this work.  The mass fractions of salt in the total mixture are 5%, 10% and 20%.  It is noted that the equilibrium between phases is modified preferably to the extracted phase and the salting-out in the case of sodium sulfate is more significant than the effect of chloride.